Perceived Impacts of Continuous Professional Development (CPD) of Teachers: A Case Study in Public Schools of District Faisalabad - Umar Farooq; Dr. Shafqat Rasool; Dr. Muhammad Shabbir (Dialogue Social Science Review (DSSR), 2025)
This investigation aims to determine how continuing professional development CPD programs affect teacher professional advancement in public primary schools operating within District Faisalabad. The researcher selected 31 public primary schools through convenient sampling from the total 179 schools. An attained sample proportion of one hundred and four teachers was chosen from a target population of one hundred and twenty-three teachers through an online tool designed to determine samples with 5% methodological error at 95% confidence level. SPSS was used to analyze the survey results collected through standardized questionnaire assessments. The study creates a distinct understanding of how classroom learning activities build up teaching methods. Such activities lead to enhanced teaching performance which produces better results in student attitudes along with SLOs and academic performance. New training modules under training/orientation combined with training/mentoring provided effective sources which enhanced both teacher performance and student educational achievements. The researchers used standard deviation and average with percentage to evaluate data statistics. The findings were presented through both percentages and means and standard deviations. Some essential factors influencing primary school teacher CPD emerged from the research study. The set of quantitative results gave recommendations for additional training requirements for level teachers. The collected data shows primary teachers believe maintaining their development requires participating in ongoing professional activities that benefit their learning students.